2017
DOI: 10.1002/cncr.30539
|View full text |Cite
|
Sign up to set email alerts
|

Unique prevalence of oncogenic genetic alterations in young patients with lung adenocarcinoma

Abstract: Younger patients with adenocarcinoma have a distinctly unique prevalence of oncogenic GAs. Comprehensive oncogenic GA screening is especially recommended for personalized medicine strategies in this population. Cancer 2017;123:1731-1740. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
76
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(100 citation statements)
references
References 37 publications
14
76
10
Order By: Relevance
“…As reported previously, EGFR mutations, the most common target gene of lung adenocarcinoma, represented 75% of all the gene alterations and occurred more frequently in females, patients who had never smoked, the elderly, and acinar predominant adenocarcinoma (16)(17)(18)(19). Interestingly, Hong et al (20) found that EGFR mutations were significantly more frequent in tumors with GGO than in solid tumors, which was contrary to our findings.…”
Section: Discussioncontrasting
confidence: 97%
“…As reported previously, EGFR mutations, the most common target gene of lung adenocarcinoma, represented 75% of all the gene alterations and occurred more frequently in females, patients who had never smoked, the elderly, and acinar predominant adenocarcinoma (16)(17)(18)(19). Interestingly, Hong et al (20) found that EGFR mutations were significantly more frequent in tumors with GGO than in solid tumors, which was contrary to our findings.…”
Section: Discussioncontrasting
confidence: 97%
“…In striking contrast to the driver landscape of Asian never‐smokers dominated by EGFR mutations, only 25.0% patients in our cohort were featured with activating EGFR . The discrepancy might be ascribed to younger age; however, previous studies concerning the difference of proportion of EGFR mutations between young and old patient groups were inconclusive . In addition, other fairly frequent events (e.g., TP53 , KRAS and KEAP1 ) in the TCGA cohort did not appear frequent in our cohort, which also demonstrated heterogeneity exist in the specific subgroup of NSCLC.…”
Section: Discussioncontrasting
confidence: 71%
“…However, only a few studies have investigated the genomic alterations of NSCLC occurring in young patients, and all of them focused on the mutational frequency of several certain driver events involved in lung cancer. Compared with older patients with NSCLC, higher incidence of ALK , ROS1 and RET fusions exist among the younger patients …”
mentioning
confidence: 98%
See 2 more Smart Citations